Facing Racism, Leaving Multiculturalism: Afro-Colombian, Black, Palenquero, and Raizal People’s (In)visibilities in Colombian Museums - Sofia Natalia Gonzalez Ayala (The February Journal, 2024)
This imaginary guided tour gathers chronologically some of the ways Black, Afro-Colombian, Palenquero, and Raizal communities or people in Colombia have appeared represented—visible and invisible—in Colombian museums between 1994 and 2023. The author reflects on exhibitions (one of which she participated in), artworks, and books to show how a multicultural vision of the nation in museums has helped maintain a neutral memory that hides the dire consequences of the transatlantic slave trade among Afro-descendants. She also works to recompose a pathway for more radical, anti-racist, and reparative initiatives that tackle and question racism and racist stereotypes in museums and exhibitions, an endeavor that requires collective and collaborative actions between public and private institutions, involving Afro- and non-Afro-descendant scholars, artists, activists, curators, researchers, designers, and writers.